Novel 2D and 3D imaging of internal aerated structure of ultrasonically treated foams and cakes using X-ray tomography and X-ray microtomography. (August 2016) - Tan, M.C.; Chin, N.L.; Yusof, Y.A.; Abdullah, J.
Abstract: The aerated structure of ultrasound treated foams and its resulted cake structures were examined using X-ray tomography and X-ray microtomography, leading to highly contrasted two-dimensional (2D) and three-dimensional (3D) images. Through these imaging techniques and software approaches, the effect of ultrasound treatment on the bubble size distribution was distinguished clearly. Microbubbles in foam which were in the size range of 0–0.00125 mm 3 and in cakes which were in the range of 0–1 mm 2 increased by 48% and 29% respectively after ultrasonic treatment at a frequency of 20 kHz. Highlights: 2D and 3D images of highly aerated foams and cakes by nondestructive X-ray tomography and X-ray microtomography techniques. The ultrasound treatment was helpful in increasing the number of microbubbles with more even distribution. Images of ring defect in cake due to dense and coarse structure.